(untitled) (Global Journal of Medical Research, 2016)
Amyloidosis is a rare disorder caused by deposition of amyloid fibrils in various tissues causing structural and functional defects. Depending upon organs involved, it may be categorized as localized or systemic. Systemic amyloidosis involves multiple organs where some organs are affected more commonly than others. Diagnosis is often challenging as in a 76-yearsold female described here who presented with intractable nausea and vomiting. Clinical course was complicated because of simultaneous presence of peptic ulcer disease and hypothyroidism. Involvement of multiple systems including gastrointestinal tract, thyroid, liver, heart and kidneys was seen, and diagnosis was achieved after renal biopsy showing Congo red staining and apple green birefringence. Gastric and thyroid infiltration by amyloidosis are extremely rare occurrences described very infrequently in the literature. However, to our knowledge, involvement of both organs in a single patient has not been reported in the literature.